ChemInform Abstract: I2‐Mediated Oxidative C—O Bond Formation for the Synthesis of 1, 3, 4‐Oxadiazoles from Aldehydes and Hydrazides. Issue 13 (1st April 2014) - Yu, Wenquan; Huang, Gang; Zhang, Yueteng; Liu, Hongxu; Dong, Lihong; Yu, Xuejun; Li, Yujiang; Chang, Junbiao
Abstract Coupling of aldehydes and hydrazides followed by I2‐mediated cyclization offers a simple, convenient, and environmentally friendly method to prepare symmetrically and asymmetrically substituted oxadiazoles.